Comparison of toxicity of Ti3C2 and Nb2C Mxene quantum dots (QDs) to human umbilical vein endothelial cells. Issue 5 (13th October 2020) - Gu, Manyu; Dai, Zhiqi; Yan, Xiang; Ma, Junfei; Niu, Yingchun; Lan, Wenjie; Wang, Xin; Xu, Quan
Abstract: Recently, we developed highly fluorescent Ti3 C2 and Nb2 C Mxene quantum dots (QDs) for labeling of in vitro models. However, the mechanism of the toxicity of the prepared QDs was not explored before. In this study, we addressed the possible mechanism associated with cytotoxicity of the QDs to human umbilical vein endothelial cells (HUVECs). Exposure to up to 100 μg/ml Ti3 C2 but not Nb2 C QDs for 24 h significantly induced cytotoxicity. The exposure also increased intracellular Ti and Nb elements, indicating the internalization of both types of QDs. None of the QDs promoted interleukin 6 (IL‐6) and IL‐8 releases. Rather, Ti3 C2 QDs significantly reduced IL‐6 and IL‐8 release, indicating that the toxicity of Ti3 C2 QDs was not due to elevated inflammatory responses. Exposure to Ti3 C2 but not Nb2 C QDs resulted in increased LC3B‐II/I ratio and beclin‐1 proteins, biomarkers of autophagy, as well as the accumulation of autophagic substance p62. Ti3 C2 QDs also more effectively promoted pro‐caspase 3 but not pro‐caspase 8 compared with Nb2 C QDs. Furthermore, pre‐treatment with autophagic modulators altered the cytotoxicity of Ti3 C2 QDs, which further confirmed the role of autophagic dysfunction in Ti3 C2 QD‐induced toxicity to HUVECs. In conclusion, the results from this study suggested that high levels of Ti3 C2 QDs could induce cytotoxicity to HUVECs by inducing the dysfunction of autophagy. Nb2 C QDs appeared to be more biocompatible to HUVECs compared with Ti3 C2 QDs at the same mass concentrations, which suggested a role of composition of Mxene QDs to determine their toxicity to human endothelial cells. Abstract : This study investigated the mechanisms of toxicity of Ti3 C2 and Nb2 C Mxene quantum dots (QDs) to human umbilical vein endothelial cells (HUVECs). Ti3 C2 but not Nb2 C QDs induced cytotoxicity. Ti3 C2 QDs promoted LC3B‐II/I, beclin‐1, p62, and pro‐caspase 3, whereas Nb2 C QDs showed little to no effect on these proteins. Furthermore, pre‐incubation with autophagic modulators altered the toxicity of Ti3 C2 QDs to HUVECs. Thus, Ti3 C2 but not Nb2 C QDs induced cytotoxicity to HUVECs due to autophagic dysfunction.